Safety and efficacy of dexpramipexole in eosinophilic asthma: a comparative study in a tertiary care hospital in Bangladesh - Islam, M. Anarul; Ullah, Muhammad Aman; Hassan, Rashedul; Alam, Moshiul; Uddin, Muhammad Salah; Hoq, Abu Jafar M. Shahidul (International Journal of Research in Medical Sciences, 2025)
Introduction: Eosinophilic asthma is characterized by elevated eosinophil levels and frequent exacerbations, which are difficult to control with standard therapies. Dexpramipexole, an oral small molecule, has shown promise in reducing eosinophil counts, but data on its long-term efficacy and safety are limited. This study aimed to evaluate the efficacy and safety of Dexpramipexole in patients with eosinophilic asthma, focusing on changes in blood eosinophil counts, lung function, quality of life, and asthma exacerbation rates. Methods: This was a cross-sectional observational comparative study conducted at the department of Reparatory Medicine during January-2021 to December-2021, in Uttara Adhunik Medical College Hospital, Dhaka Bangladesh. A total of 200 confirmed cases with eosinophilic asthma were purposively employed to receive Dexpramipexole (n=100) and placebo (n=100) for 12 months follow up. The collected data were analyzed using Statistical Package for Social Sciences (SPSS), version-23.0. Results: The Dexpramipexole group achieved a 75% reduction in eosinophil counts compared to 12% in the placebo group (p<0.001). FEV1 improved by 15% in the Dexpramipexole group versus 2% in the placebo group (p<0.01). Quality of life scores increased by 1.5 points compared to 0.3 points in the placebo group (p<0.001). A 30% reduction in asthma exacerbations was observed (p=0.03). Conclusion: Dexpramipexole demonstrated significant improvements in eosinophil reduction, lung function, quality of life, and exacerbation rates over a 12-months period, with a favorable safety profile. These results suggest Dexpramipexole may be a promising long-term therapeutic option for eosinophilic asthma.